TANTANGAN DAN PELUANG DALAM PENGEMBANGAN BALAI LATIHAN KERJA KOMUNITAS MELALUI PENDIRIAN INKUBATOR WIRAUSAHA DI WILAYAH II JAWA BARAT - Turasih, Turasih; Hasim, Wakhit; Handayani, Amelia Dwi; Ramdaeni, Suci (Holistik: Journal for Islamic Social Sciences, 2024)
Community Vocational Training Centers (BLK-K) are one of the backbones of unemployment alleviation through job creation and the creation of entrepreneurs capable of producing products or services. This study aims to analyze the characteristics, challenges, and opportunities of BLKK in 12 regencies/cities within Region II in West Java in their development through the establishment of entrepreneurial incubators. The study used a mixed method that combines qualitative and quantitative approaches. Primary resources were drawn from the direct BLK-K actors, the mentoring team, officers from the Bandung Center for the Acceleration and Expansion of Employment Opportunities, and related BLK-K/incubator tenants. Secondary data sources were drawn from literature reviews and various sources related to Community BLK and entrepreneurial incubators. Qualitative data collection methods were carried out through direct observation of several BLK K locations, interviews during mentoring, FGDs, and literature reviews. Meanwhile, the quantitative approach utilized a questionnaire instrument to obtain data on BLK-K attitudes towards external challenges and opportunities. The results showed that there are 23 BLK-K in 12 regencies in West Java that have developed and established entrepreneurial incubator institutions characterized by Islamic boarding school-based management. The main characteristics of the development of BLK-K into an entrepreneurial incubator are having a strategic plan for an entrepreneurial incubator, having a set of standard operating procedures (SOPs) as guidelines for activities, and having entrepreneurial tenants around the Islamic boarding school. In its development, BLK-K still faces challenges in the form of dependence on funding from the central government, limited cooperation with the business world and the industrial world, BLK-K management, training quality, instructor competence, location selection and vocational programs, and the continued resistance to change. However, there are opportunities that BLK-K can take advantage of, including increasing BLK-K capacity, multi-party collaboration, and the development of communication and information technology.